KARAKTERISTIK PETANI NANAS BESERTA INPUT, MODAL, DAN PENDAPATANNYA: STUDI DESKRIPTIF DAN KORELATIF - Elly Rasmikayati; Endah Djuwendah; Bobby Rachmat Saefudin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Farming activities aim to increase productivity so that profits will be higher. Production and productivity cannot be separated from the production factors owned by farmers to increase the production of their crops. The purpose of this study was to describe the characteristics of pineapple farming and the relationship between farmer characteristics, namely land area and farming inputs, capital and farming income. The data used in this study were 42 farmers in Astomulyo Village, Punggur District, Central Lampung. Data were analyzed using descriptive statistics, cross tabulation and chi-square analysis. The results showed that farmers with large land areas (> 1 Ha) produced high pineapple production using 41 thousand - 60 thousand seeds and farming income of more than 100 million per year, but costs for rent and production were categorized as high, above 10 million. Farmers who have medium land (0.5 - 1 Ha) use as much as 21 thousand - 40 thousand seeds with the majority of farm income generated exceeding 100 million, but the cost of renting the land is quite high, which is 10 million/year and high input costs exceed 10 million/year. Farmers who have small land (<1 Ha) use seeds ranging from 10 thousand - 20 thousand, have limited land, earn less than 50 million/year, cheap rent costs less than 5 million/year and farming costs less than 10 million/year. Based on the results of comparative analysis, it can be concluded that there is a significant relationship between land area and stem seed farming inputs, total income, farming costs (rent), and farming costs (saprotan) at a significant level of 5%.